Smart Horticulture: Latest Advances and Prospects - Alessia Cogato; Marco Sozzi; Nebojša Nikolić; Eve Laroche-Pinel (Horticulturae)
The latest Hunger Hotspots Report by the Food and Agriculture Organisation (FAO) and the World Food Programme (WFP) of the United Nations highlighted 16 hotspots in which food insecurity is increasing due to conflict, economic instability, and extreme weather events [...]